(untitled) (Al-Qamar, 2022)
The religion of Islam is a complete code of life in which all human beings have solution of its problem. The long-standing problem in our country is economy. We can solve our economic problems by obeying the teaching of Islamic. Hazrat Umar Farooq (RA) made the Islamic Empire strong and stable by using the principles set by the Prophet ﷺ regarding the economy. During the caliphate of Hazrat Umar Farooq (RA) a detailed plan can be seen in the finance and economic departments. Natural disasters such as famine and plague were dealt and controlled. Many measures were taken in the field economy for the prosperity of the people. He abolished feudalism and decided not to distribute tributary lands of conquered areas. The allotment of uninhabitable lands was decided and enabled the Baitul-mal. Arranged salaries and affairs of government, fixed the salaries of mujahideen. fixed the expenses of Amal and the caliph. He fixed the stipends for the wives of the mujahideen. The roles and regulation of economic systems of Hazrat Umar Farooq (R.A) does not mean only that a blueprint to be implemented in Pakistan. But rather these are the basic rules that are described in the book of Allah and Sunnah ﷺ. The interpretations of these roles have been interpreted from time to time by the imam’s mujahidin since the time of the companions and the Tabieen and the entire Ummah agrees on them. Hazrat Umar Farooq’s (R.A) economic ideas were not only specific to that era but even today the laws of that era can be implemented and the same blessed results can be achieved.